Evaluative study of the Kurikulum Merdeka learning system in Bandung Private Elementary Schools - Endang Purwati; Zainal Arifin (Curricula: Journal of Curriculum Development, 2023)
An educational institution is considered successful if it can be measured from the evaluation activities’ success. This research was conducted to evaluate the implementation of the independent curriculum using the Countence Stake evaluation model which focuses on antecedents, transactions, and outcomes. The sample used consisted of 26 respondents consisting of school principals, class teachers, and subject teachers at private elementary schools in Bandung City who implemented the Merdeka Curriculum starting in the 2022-2023 school year simultaneously from phases A, B and C. The sample was taken using the purposive sampling method, which was taken manually by the way the respondents filled out the distributed questionnaire forms. Based on the research, it shows that (1) the process of learning the independent curriculum in elementary schools is quite effective, although its implementation is still not optimal; (2) The obstacles to implementing the independent curriculum include the use of textbooks as learning resources; (3) Designing better learning strategies is needed. From this study it can be concluded that teachers must be more creative in guiding students in projects and can inspire them to develop their potential and instill character values. In addition, teachers must develop their skills so that they can carry out fun learning.   Abstrak Suatu instansi pendidikan dinilai berhasil apabila dapat diukur dari keberhasilan kegiatan evaluasi yang dilakukan. Penelitian ini dilakukan untuk mengevaluasi pelaksanaan kurikulum merdeka dengan menggunakan model evaluasi Countence Stake yang menitikberatkan pada antecedent, transaction, dan outcomes. Sampel yang digunakan terdiri dari 26 responden yang terdiri dari kepala sekolah, guru kelas dan guru mata pelajaran di SD Swasta Kota Bandung yang menerapkan Kurikulum Merdeka mulai tahun ajaran 2022-2023 secara serentak dari fase A, B dan C. Sampel diambil menggunakan metode purposive sampling, yang diambil secara manual dengan cara responden mengisi form kuesioner yang dibagikan. Berdasarkan penelitian menunjukkan bahwa (1) Proses pembelajaran kurikulum merdeka di sekolah dasar berjalan cukup efektif, meskipun penerapannya masih belum optimal; (2) Kendala penerapan kurikulum merdeka antara lain penggunaan buku teks sebagai sumber belajar; (3) Perancangan strategi pembelajaran yang lebih baik dibutuhkan. Dari penelitian ini dapat disimpulkan bahwa guru harus lebih kreatif dalam membimbing siswa dalam proyek dan dapat menginspirasi mereka untuk mengembangkan potensi dan penanaman nilai karakter. Selain itu, guru harus mengembangkan keterampilannya agar dapat melaksanakan pembelajaran yang menyenangkan. Kata Kunci: evaluasi program; implementasi kurikulum merdeka; model countenance stake